The impacts of Covid-19 on macroeconomic indicators and the performance of Islamic banks in Indonesia - Ulumuddin Nurul Fakhri; Aminah Nuriyah (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – The purpose of this study was to determine the extent of the impact of Covid-19 on the macroeconomic indicators and financial performance of Islamic banks in Indonesia. The results of this study may serve as a reference for the Indonesian government and Islamic banks’ stakeholders in formulating strategic decisions in creating innovative solutions during the Covid-19 pandemic.Methodology – Quantitative research method with 2 approaches, namely Partial Least Square-Structural Equation Modeling (PLS-SEM) and Artificial Neural Networks (ANN) was selected for this study.Findings – This study demonstrated that macroeconomic indicators were significantly affected by the Covid-19 pandemic. However, the results of the ANN and PLS-SEM models varied. The PLS-SEM model illustrated the impact of the Covid-19 pandemic affecting the performance of Islamic banking, while the ANN model did not.Implication – This research has implications for stakeholders, especially the government to maintain macroeconomic stability, while for Islamic banking management to focus more on product innovation and service excellence so that it can be closer to the public, especially Muslims community.Originality – Numerous studies examining macroeconomics and the financial performance of Islamic banking have been conducted. This study aimed to offer an alternative perspective by using two models, namely PLS-SEM and ANN.